(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Monometallic nickel(II) complexes [Ni(H2nsh)(A)2]•nH2O (where A = water (H2O)n=0 (1), (1) pyridine (py), n=2 (2) 2-picoline(2-pic), n=0(3) 3-picoline(3-pic), n=2 (4) and 4-picoline(4-pic), n=0 (5) and homobimetallic nickel(II) complexes [Ni2(nsh)(A)4]•H2O (where A = water (nH2O), n=1(6) pyridine(py), n=4(7) 2- Elemental measurements, molar conductance, magnetic moment, and electrical and IR and TGA DTA spectroscopic experiments have described the complexes. Monometallic complexes (1) to (5) have octahedral stereochemistry, while complexes (6) to (10) have distorted octahedral stereochemistry, where one of the Ni(II) centres is present in the coordination sphere of N2O2 and another Ni(II) centre is bound to it by oxo-bridging by phenolate oxygen atoms.